The Impact of Gross Regional Product Per Capita on the Processes of Convergence between Different Regions of the Country - Mayya Dubovik; Sergey Dmitriev; Madina Aitkazina (Qubahan Academic Journal)
The purpose of this study was to analyses the dynamics of gross regional product per capita within the regions of Russia from 2005 to 2020, with the objective of examining the presence of convergence among these administrative and territorial units. Beta and sigma convergence methodologies were utilized. Beta convergence refers to the tendency of poorer regions or countries to grow faster than richer ones, leading to income equalization. Sigma convergence indicates a reduction in disparities between regions or countries over time, reflected in decreasing income variance. Those concepts are relevant for Russia as they highlight the potential for reducing regional economic disparities and fostering balanced growth across its diverse regions.  The speed of convergence was calculated using both ordinary least squares and nonlinear least squares methods, revealing that eliminating a 50% gap in GRP per capita among Russian regions would take approximately 902 and 821 years, respectively. Thereby, evidence of sigma convergence was not found, implying that the inequality among these regions remained statistically insignificant from 2005 to 2020. The analyzed period was characterized by divergent processes within the economy of the Russian regions. The study fills the gap by highlighting the absence of sigma convergence, indicating persistent inequality in economic results across Russian regions despite globalization trends that typically contribute to convergence. Further research is necessary to understand the underlying reasons for this divergence.